Review of perspective space debris mitigation solutions. Issue 1 (March 2023) - Usovik, I.V.
Abstract: Space debris poses an increasing threat to functioning spacecraft every year. In order to solve problems created by space debris and make administrative decisions, it is necessary to assess impact of various measures taken to mitigation and remediation on space debris environment. The article presents an overview of promising methods for limiting of space debris and methods developed by author that allow for a detailed assessment of various space debris sources and measures contribution to space debris environment.